Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
When using substitution, you have to make sure only one variable is on one side of the equation in this case, the easiest way to do this would be to isolate s in the equation 2r+s=11.
When you do this, you should get:
s=-2r+11
Now you can plug in the value of s into the equation 6r-2s=-2. You should come up with:
6r-2(-2r+11)=-2
Now use the distributive property and solve for r:
6r+4r-22=-2
10r-22=-2
10r=10
r=1
Now that you have found the value of r, you can plug it into one of the first equations to solve for s:
2(1)+s=11
2+s=11
s=9
So the solution to the system is r=1 and s=9.
Hope I helped! :)
When you do this, you should get:
s=-2r+11
Now you can plug in the value of s into the equation 6r-2s=-2. You should come up with:
6r-2(-2r+11)=-2
Now use the distributive property and solve for r:
6r+4r-22=-2
10r-22=-2
10r=10
r=1
Now that you have found the value of r, you can plug it into one of the first equations to solve for s:
2(1)+s=11
2+s=11
s=9
So the solution to the system is r=1 and s=9.
Hope I helped! :)
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.